The Audit Truth - Murat, Leszek (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Each lawful audit centers on discovering truth. Often times, revealing facts is far from ideal and entails some kind of truth creation, called by the author “the audit truth”. The audit statements of facts create their own normative and semantic reality. The audit truth is always to some degree subjective, uncertain, approximated and simplified. Nonetheless, it does not make it false. Imperfectness of reality’s description is hard to avoid. As such it has to be accepted only if it meets certain standards of discovery and description. The article, by revealing the nature of the audit truth, fills the gap in the literature that so far has been focused on the principle of the material truth as an ideal goal for auditors. The author argues that pursuing truth in audit deserves advanced and systematic studies by audit philosophy.